Effect of Adapted Story on Developing Listening, Speaking, Reading and Writing (LSRW) Skills for Preschool Children with Hearing Impairments - K.R., Subramanya; Upadhyay, Alok Kumar (JOURNAL OF INDIAN EDUCATION, 2026)
Background: Nursery Story and rhymes enhance phonological sensitivity which in turn enhances communication skills and linguistic development. Objective: To identify the effectiveness of adapted story for developing Learning, Speaking, Reading and Writing (LSRW) skills for children with hearing impairments. Sample: Children with hearing impairments at the age of 3 to 4 years availing training at AIISH, Mysuru. Design: One group pre-test post-test experimental design was employed to examine the effect of adapted story on developing LSRW skills at an early age. Results and Discussion: From the observation of the pre-test and post-test result, the result shows that the adapted story is more effective. It implies that adapted story can help develop LSRW skills at an early age through different activities for children with special needs. Conclusion: It can be said that story will be more effective for developing listening, speaking, pre-reading and pre-writing skills with necessary support and facilities